LONG-TERM CHANGES OF GROUND FAUNA OF COASTAL ZONES OF APSHERON AND BAKU ARCHIPELAGOES ISLANDS OF CASPIAN SEA DURING 1967-2007 - R. M. Bagirov; V. R. Gourbanova (Юг России: экология, развитие)
During 2000-2007 studying of specific structure macrozoobenthos and its quantitative distribution on islands of Apsheron and Baku archipelagoes of Caspian Sea has been spent. The got results have been compared with the results of analyses carried out in the same area of the sea between 1967-1986 years, and as a result, increasing in quantity and bio weight of bottom fauna has been observed. Number of macroorganisms has increased in 20 times, and a biomass - in 15 times. The oil maintenance in waters for the first 20 years has decreased with in 1,2-2 times, for the next 20 years quantity of oil has decreased in limits from 10 to 300 times. Considering the above-stated, it is possible to come to conclusion about absence now appreciable negative consequences for sea ecosystem and bioresources of Caspian Sea from working out of oil and gas deposits.